2012
DOI: 10.5336/medsci.2011-25802
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Liver Fibrosis in Patients with Chronic HCV Infection

Abstract: A AB BS ST TR RA AC CT T O Ob bj je ec ct ti iv ve e: : The aim of this study was to investigate the independent variables for the degree of liver fibrosis in patients with chronic hepatitis C virus (HCV) infection. M Ma at te er ri ia al l a an nd d M Me et th ho od ds s: : In this cross-sectional retrospective study, the patients were divided in two groups as Group A (patients with fibrosis score 0-2) and Group B (patients with fibrosis score 3-4) and they were compared in terms of age, gender, body mass ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 36 publications
1
16
0
4
Order By: Relevance
“…These studies reported that the decline in serum HBV DNA levels and HBV DNA negativity rates were not different between TDF and ETV treatments for CHB (26,27). A recent meta-analysis also confirmed that no differences were observed in the ALT normaliza- tion rates and HBeAg seroconversion rates after 24 weeks and 48 weeks of TDF or ETV therapy (28).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…These studies reported that the decline in serum HBV DNA levels and HBV DNA negativity rates were not different between TDF and ETV treatments for CHB (26,27). A recent meta-analysis also confirmed that no differences were observed in the ALT normaliza- tion rates and HBeAg seroconversion rates after 24 weeks and 48 weeks of TDF or ETV therapy (28).…”
Section: Discussionsupporting
confidence: 50%
“…There are some observational studies comparing TDF and ETV in terms of their antiviral responses to CHB (26,27). These studies reported that the decline in serum HBV DNA levels and HBV DNA negativity rates were not different between TDF and ETV treatments for CHB (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…The use of tenofovir and entecavir was compared in 13 studies with average sample sizes of 62 per treatment group (range, 22‐148). The first RCT of HBV‐infected adults with decompensated cirrhosis showed no significant difference in serum creatinine or creatinine clearance over 48 weeks of tenofovir (n = 45) or entecavir (n = 22) . The second RCT of 200 HBV‐infected adults (100 on tenofovir, 100 on entecavir) showed no significant decline in renal function and no difference in adverse events .…”
Section: Renal and Bone Disease In Persons On Na Therapymentioning
confidence: 99%
“…Si bien, se han publicado estudios que comparan directamente ambas opciones de tratamiento (24)(25)(26)(27)(28)(29)(30)(31) existen algunas comparaciones indirectas reportadas en distintos metaanálisis en red, que definen una jerarquía en la eficacia de los agentes antivirales (32)(33)(34) . Para el presente análisis se han considerado los resultados del metaanálisis en red más reciente (18) respecto de las opciones antivirales para HBV crónica, el que comprendió un total 21 pares de comparación con 5073 pacientes näive de tipo HbeAg positivo y 16 pares de comparación con 2604 pacientes näive de tipo HbeAg negativo.…”
Section: Discussionunclassified